2021
DOI: 10.1155/2021/6493712
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Transverse Process-Pedicle Approach Applied to Unilateral Extrapedicular Percutaneous Vertebroplasty

Abstract: Objective. To introduce a modified transverse process-pedicle puncture technique applied to unilateral extrapedicular percutaneous vertebroplasty (PVP) for the treatment of osteoporotic lumbar vertebral compression fractures. Methods. A retrospective study was performed on 91 patients with osteoporotic vertebral compression fractures (OVCFs) who underwent unilateral extrapedicular PVP from June 2016 to September 2018. Lumbar and back pain was assessed through the visual analogue scale (VAS). Function recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Andrew J. Ringer and Sunita V. Bhamidipaty [33] rst report step-by-step the percutaneous techniques used in the lumbar and thoracic extrapedicular approaches and the thoracic infrapedicular approach, with depiction in accompanying video presentation. Liu and Zhang et al [34,35] introduced that the puncture methods in different extrapedicular approaches and recommend appropriate extrapedicular puncture methods for thoracolumbar PVP (PKP). However, the complications between two different approaches of percutaneous kyphoplasty were the main points that attracted the attention of those making the decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Andrew J. Ringer and Sunita V. Bhamidipaty [33] rst report step-by-step the percutaneous techniques used in the lumbar and thoracic extrapedicular approaches and the thoracic infrapedicular approach, with depiction in accompanying video presentation. Liu and Zhang et al [34,35] introduced that the puncture methods in different extrapedicular approaches and recommend appropriate extrapedicular puncture methods for thoracolumbar PVP (PKP). However, the complications between two different approaches of percutaneous kyphoplasty were the main points that attracted the attention of those making the decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Bone cement diffuses across the midline; both sides of the vertebra can increase stiffness significantly, and biomechanical balance of stress on both sides is achieved [ 24 ]. The extrapedicular approach of the transverse process increases the puncture angle [ 5 25 ]; however, the limitations of the skin entry point and injury to the ligament complex and segmental artery make the application of this approach relatively limited [ 6 7 ]. Furthermore, Wang et al [ 26 ] reported that the Kambin triangle approach is safe and effective and has excellent cement distribution in osteoporotic vertebral compression fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical interventions typically involve unilateral or bilateral percutaneous vertebroplasty (PVP), in which polymethylmethacrylate is injected into the fractured vertebra to alleviate pain and correct kyphosis ( 5-7 ). While unilateral vertebroplasty has benefits such as a shorter duration of surgery and reduced radiation exposure when compared with bilateral PVP, it often results in uneven bone cement distribution ( 8 ). To achieve a more even cement spread, the abduction angle of the metal puncture rod is typically increased during unilateral puncture, which could theoretically elevate the risk of spinal cord injuries.…”
Section: Introductionmentioning
confidence: 99%